Sodium ion positive electrode material and preparation method thereof, positive electrode plate and battery

By adopting a sodium ion positive electrode material with an O3 phase structure and doping it with Cu, Zn and M elements, the problem that the sodium ion positive electrode material in the prior art is difficult to improve capacity while reducing costs, and achieving high cost-effectiveness and excellent cycle retention performance.

CN119674054APending Publication Date: 2025-03-21BEIJING HINA BATTERY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656764.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing sodium ion layered oxide cathode materials are difficult to increase capacity while reducing costs, resulting in low cost performance.

Method used

The sodium ion positive electrode material with O3 phase structure has a chemical formula of Na10/12+2x+2yNi3/12±0.01Fe4/12±0.01Mn5/12±0.01CuxZnyMzO2 (1+x+y+z), and by doping Cu, Zn and M elements (such as Ti) to reduce nickel content, improve capacity and structural stability.

Benefits of technology

It is achieved to increase the capacity of sodium ion cathode material while reducing costs, improve the cost-effectiveness of the material, and significantly improve the circulation retention performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674054A_ABST
    Figure CN119674054A_ABST
Patent Text Reader

Abstract

The chemical formula of the sodium ion positive electrode material is Na < 10 > / 12 + 2x + 2y > Ni < 3 > / 12 + / -0.01 Fe < 4 > / 12 + / -0.01 Mn < 5 > / 12 + / -0.01 Cu < x > Zn < y > M < z > O < 2 > (1 + x + y + z), the content satisfies Ni + Fe + Mn = 1, x is greater than 0 and less than or equal to 0.08, y is greater than 0 and less than or equal to 0.04, M contains Ti, and the content of M satisfies 0 and less than or equal to 0.05. The sodium ion positive electrode material provided by the invention has relatively high capacity while reducing the cost, can effectively improve the structural stability of the ion positive electrode material, and has relatively excellent cycle retention rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a sodium ion positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] Since sodium ions have the advantages of abundant resources and cheap raw materials, sodium ion secondary batteries are considered to be very likely to replace lithium ion secondary batteries, which can solve the problem of lithium resource shortage, thereby achieving cheap large-scale energy storage and large-scale commercial applications.

[0003] One of the core issues facing current sodium-ion layered oxide cathode materials is how to increase capacity while reducing costs. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a sodium ion positive electrode material and a preparation method, a positive electrode plate and a battery, which can reduce the cost while increasing the capacity.

[0005] According to the sodium ion positive electrode material of the first embodiment of the present invention, the sodium ion positive electrode material is an O3 phase structure, and the chemical formula of the sodium ion positive electrode material is Na 10 / 12+2x+2y Ni 3 / 12±0.01 Fe 4 / 12±0.01 Mn 5 / 12± 0.01 Cu x Zn y M z O 2(1+x+y+z) , wherein Ni+Fe+Mn=1, 0<x≤0.08, 0<y≤0.04, M includes Ti, and the content of M satisfies 0<z≤0.05.

[0006] The sodium ion positive electrode material of the embodiment of the present invention has a low nickel content, and low nickel content is the key to reducing costs; at the same time, it also has a high capacity, which can meet the industrialization needs of gradually increasing capacity while continuously reducing costs, and has a high cost performance. Moreover, the doping of Cu and Zn elements effectively improves the capacity of low-nickel positive electrode materials. In addition, the doping of M elements can effectively improve the structural stability of the ion positive electrode material, so that the sodium ion positive electrode material exhibits a better cycle retention rate performance.

[0007] Optionally, M further contains a Zr element.

[0008] Optionally, the sodium ion positive electrode material has a specific capacity of 2.5-4.2V, and a 0.1C reversible specific capacity of ≥160mAh / g.

[0009] Optionally, the sodium ion positive electrode material is in a single crystal morphology.

[0010] Optionally, under the conditions of 25° C. and 50% humidity, after being fully exposed for 12 hours, the pH value of the sodium ion positive electrode material is ≤12.6.

[0011] Optionally, after 100 cycles of 1C in the voltage range of 2V-4.2V, the capacity retention rate of the sodium ion positive electrode material is ≥92.5%.

[0012] According to the second aspect of the present invention, the method for preparing a sodium ion positive electrode material comprises the following steps: mixing a sodium source raw material, a nickel source raw material, an iron source raw material, a manganese source raw material, a copper source raw material, a zinc source raw material and an M source raw material; preparing the sodium ion positive electrode material by a high temperature solid phase sintering process through the mixed raw materials, wherein the sodium ion positive electrode material is any of the above-mentioned sodium ion positive electrode materials.

[0013] Optionally, the step of preparing the sodium ion positive electrode material by a high-temperature solid-phase sintering process of the mixed raw materials includes: heat-treating the mixed raw materials under an oxygen atmosphere at a high temperature of 800°C-1000°C for 10h-25h; and obtaining the sodium ion positive electrode material by crushing and screening.

[0014] According to the positive electrode plate of a sodium ion battery in the third embodiment of the present invention, the positive electrode plate comprises any of the above-mentioned sodium ion positive electrode materials.

[0015] A sodium ion battery according to an embodiment of the fourth aspect of the present invention comprises a positive electrode plate of any of the above-mentioned sodium ion batteries.

[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is the SEM morphology information of Example 1 of the present invention; Figure 2 This is the XRD information of Example 2 of the present invention. DETAILED DESCRIPTION

[0018] Reference below Figure 1 A sodium ion positive electrode material according to an embodiment of the present invention is described.

[0019] According to the sodium ion positive electrode material of the embodiment of the present invention, the sodium ion positive electrode material has an O3 phase structure, and the chemical formula of the sodium ion positive electrode material is Na 10 / 12+2x+2y Ni3 / 12±0.01 Fe 4 / 12±0.01 Mn 5 / 12±0.01 Cu x Zn y M z O 2(1+x+y+z) , where the element content ratio of Ni, Fe and Mn is Ni:Fe:Mn=3:4:5, and Ni+Fe+Mn=1, 0<x≤0.08, 0<y≤0.04, M includes Ti, and the content of M satisfies 0<z≤0.05. In other words, M includes Ti, and the single element content fluctuation range of Ni, Fe and Mn is ±0.01. Figure 2 As shown, the XRD spectrum of the sodium ion positive electrode material shows that it has a pure O3 phase structure.

[0020] In other words, in this embodiment, the sodium ion positive electrode material contains Ni, Fe and Mn elements, forming a ternary system in the battery field. Among them, the main function of Mn is structural support, which is beneficial to maintain the structural stability of the material. Moreover, the sodium ion positive electrode material is also doped with Cu, Zn and M elements, among which Cu and Zn are +2 valences, providing reversible capacity like Ni; Ti is +4 valence, and together with Mn, it plays a role in structural stability, that is, M contains at least Ti, which can assist Mn in improving the structural stability of the material and showing better cycle retention performance.

[0021] It should be noted that the Fe content should not be too much, otherwise the structural stability will deteriorate; the Mn content should not be too much, otherwise it will be difficult to provide reversible specific capacity. Therefore, in this embodiment, by combining the above elements, the Ni content can be low, thereby reducing the material cost; and a moderate Fe content can increase the reversible capacity and reduce the cost; a moderate Mn content can also provide a reversible specific capacity.

[0022] Since the content of Ni in the sodium ion positive electrode material of this embodiment is low, the reversible capacity is easily limited. Therefore, in this embodiment, the active elements Cu and Zn in the +2 valence state are introduced by doping, which can not only provide reversible specific capacity, but also improve the structural stability of the positive electrode material during the sodium deintercalation process.

[0023] Among them, the content of Cu and Zn elements satisfies 0<x≤0.08, 0<y≤0.04. It should be noted that by adopting the above-mentioned content of Cu and Zn elements, the doping of Cu and Zn elements, on the one hand, cooperates with the Ni element with the same +2 valence state to provide reversible capacity, and at the same time, Cu and Zn are cheaper than nickel. As active elements, they are introduced into the material system for reasonable matching, which can effectively improve the physical and chemical properties and improve the cost performance of the material; but too much introduction will cause a significant decrease in performance. Therefore, in this embodiment, by adopting the content of Cu and Zn elements to satisfy 0<x≤0.08, 0<y≤0.04, for example, the content of Cu element is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07 or 0.08, etc.; the content of Zn element is 0.01, 0.02, 0.03 or 0.04, etc., which can not only improve the reversible capacity, but also reduce the production cost, and avoid a significant decrease in performance.

[0024] In addition, the content of the M element satisfies 0<z≤0.05, for example, z is 0.01, 0.02, 0.03, 0.04 or 0.05, etc. If the Zr content is greater than 0.05, the cycle performance and air stability are easily affected.

[0025] Therefore, the sodium ion positive electrode material according to the embodiment of the present invention has a low nickel content, and low nickel content is the key to reducing costs; at the same time, it also has a high capacity, which can meet the industrialization needs of gradually increasing capacity while continuously reducing costs, and has a high cost performance. Moreover, the doping of Cu and Zn elements effectively improves the capacity of low-nickel positive electrode materials. In addition, the doping of M elements can effectively improve the structural stability of ion positive electrode materials, so that the sodium ion positive electrode material exhibits better cycle retention performance.

[0026] According to one embodiment of the present invention, M also contains Zr element, Zr is +4 valence, and can play a role in structural stability together with Mn, that is, M contains Ti, or contains Ti and Zr at the same time, and the M element can assist Mn in improving the structural stability of the material, showing a better cycle retention performance. In addition, the co-introduction of Cu, Zn, Ti, and Zr elements turns the original NiFeMn ternary cathode material into a high-entropy cathode material of 7 elements, which is more conducive to forming a synergistic optimization effect.

[0027] According to one embodiment of the present invention, the specific capacity of the sodium ion positive electrode material is 2.5V-4.2V, that is, it has a higher specific capacity, for example, the specific capacity of the sodium ion positive electrode material is 2.5V, 2.8V, 3.0V, 3.5V, 4.0V or 4.2V, etc.; in addition, the 0.1C reversible specific capacity is ≥160mAh / g, and the high-capacity positive electrode material can improve the volume energy density and mass energy density of the sodium ion battery cell, reduce the battery cell cost, and improve the cost performance of the battery cell product.

[0028] In some specific embodiments of the present invention, the sodium ion positive electrode material is a single crystal morphology, such as Figure 1 shown.

[0029] According to one embodiment of the present invention, under the conditions of 25° C. and 50% humidity, after being fully exposed for 12 hours, the pH value of the sodium ion positive electrode material is ≤12.6. The sodium ion positive electrode material of this embodiment has good air stability.

[0030] In some specific embodiments of the present invention, after 100 cycles of 1C in the voltage range of 2V-4.2V, the capacity retention rate of the sodium ion positive electrode material is ≥92.5%.

[0031] The present invention also provides a method for preparing a sodium ion positive electrode material, the preparation method comprising the following steps: Mix the sodium source raw material, the nickel source raw material, the iron source raw material, the manganese source raw material, the copper source raw material, the zinc source raw material and the M source raw material. For example, the raw materials used for solid phase sintering include sodium source, nickel source, iron source, manganese source, copper source, zinc source, titanium source and zirconium source. Among them, the sodium source can be at least one of sodium carbonate and sodium bicarbonate; other metal sources can be at least one of the corresponding metal oxides, hydroxides, carbonates, bicarbonates, and mixed hydroxides, mixed carbonates, mixed oxides and other compounds.

[0032] The mixed raw materials are prepared by a high-temperature solid-phase sintering process to obtain a sodium ion positive electrode material, and the sintering temperature is not less than 800° C. It can be seen that in the present embodiment, the preparation scheme of the positive electrode material adopts a high-temperature solid-phase sintering process, and the high-temperature sintering reaches the temperature at which the raw materials are eutectic. Different element combinations will have different eutectic temperature ranges. 800° C. is the universal minimum sintering temperature, which is suitable for the proportion limit of this scheme. A lower temperature cannot eutectic to obtain the target product, that is, the low-temperature reaction is insufficient.

[0033] According to one embodiment of the present invention, preparing the sodium ion positive electrode material by a high temperature solid phase sintering process of the mixed raw materials includes the following steps: The mixed raw materials are heat-treated at a high temperature of 800°C-1000°C for 10h-25h in an oxygen atmosphere; those skilled in the art will know that 800°C-1000°C is preferably used as the sintering temperature range of sodium layered oxides. Temperatures below 800°C are not conducive to the full solid phase reaction, while temperatures above 1000°C are prone to over-sintering, and other irreversible miscellaneous structures of non-layered structures are easily formed. Similarly, different temperatures require different matching and different sintering times to ensure that sintering is fully carried out. In this embodiment, 10-25h is a relatively reasonable insulation period limit interval. If the time is too short, it is easy to cause insufficient sintering. If the time is too long, it is an unnecessary redundant design. At the same time, if the temperature is too high, too long a time is more likely to cause over-sintering to form an irreversible heterogeneous phase structure of a non-layered structure. The sodium ion positive electrode material is obtained through crushing and screening.

[0034] That is to say, the required raw materials are fully mixed according to the target ratio, heat-treated at a high temperature of 800°C-1000°C under an oxygen atmosphere for 10h-25h, and then crushed and sieved to obtain a powdery material, which is the target positive electrode material.

[0035] Specifically, we can firstly calculate the molecular formula of the target according to Na 10 / 12+2x+2y Ni 3 / 12±0.01 Fe 4 / 12±0.01 Mn 5 / 12± 0.01 Cu x Zn y M z O 2(1+x+y+z) Prepare raw materials. The raw materials include sodium source, nickel source, iron source, manganese source, copper source, zinc source, titanium source and zirconium source, wherein the sodium source includes sodium carbonate and sodium bicarbonate; other metal sources include corresponding metal oxides, hydroxides, carbonates, bicarbonates and mixed hydroxides, mixed carbonates, mixed oxides and other compounds.

[0036] Subsequently, the required raw materials are fully mixed, heat-treated at a high temperature of 800°C-1000°C in an oxygen atmosphere for 10h-25h, and the powdery material obtained by crushing and screening is the target positive electrode material.

[0037] The present invention also provides a positive electrode plate for a sodium ion battery, the positive electrode plate comprising the positive electrode material of any of the above embodiments. Since the positive electrode material of any of the above embodiments has high capacity, structural stability and cycle retention performance, the positive electrode material of the embodiment of the present invention also has the above advantages, which will not be described in detail here.

[0038] The present invention also provides a sodium ion battery, which includes the positive electrode plate of any of the above embodiments. Since the positive electrode material of any of the above embodiments has high capacity, structural stability and cycle retention rate performance, the sodium ion battery of the embodiment of the present invention also has the above advantages, which will not be elaborated here.

[0039] The present invention also provides an electrical device, which may include the sodium ion battery of any of the above embodiments. That is, the sodium ion secondary battery of this embodiment can be used in the fields of energy storage, power, consumer electronic products, etc.

[0040] The sodium ion positive electrode material according to the embodiment of the present invention is described in detail below in conjunction with specific embodiments.

[0041] Example 1 The chemical formula of the sodium ion positive electrode material of Example 1 is Na 0.973 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 , the preparation process includes: (1) Weighing and preparing raw materials according to the molecular formula and target ratio, the raw materials include sodium carbonate, nickel hydroxide, ferric oxide, manganese dioxide, copper oxide, zinc oxide, titanium dioxide, and zirconium oxide; (2) The required raw materials are fully mixed, and heat-treated at 900°C for 20 hours in an oxygen atmosphere. The powdery material obtained by crushing and screening is the target positive electrode material.

[0042] Example 2 The chemical formula of the sodium ion positive electrode material of Example 2 is Na 0.933 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.010 Zn 0.040 Ti 0.050 O 2.2 , the preparation process includes: (1) Prepare the raw materials by weighing according to the target ratio. The raw materials include sodium carbonate, nickel hydroxide, iron manganese Ni 0.250 Fe 0.333 Mn 0.417 (OH)2, copper hydroxide, zinc oxide, titanium dioxide; (2) The required raw materials are fully mixed, and heat-treated at 980°C for 12 hours in an oxygen atmosphere. The powdery material obtained by crushing and screening is the target positive electrode material.

[0043] Example 3 The chemical formula of the sodium ion positive electrode material of Example 3 is Na 1.013 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.080 Zn 0.010 Ti 0.040 O 2.26 , the preparation process includes: (1) Prepare the raw materials by weighing according to the target ratio. The raw materials include sodium bicarbonate, nickel hydroxide, iron manganese Ni 0.250 Fe 0.333 Mn 0.417 (OH)2, copper hydroxide, zinc oxide, titanium dioxide; (2) The required raw materials are fully mixed, and heat-treated at 820°C for 25 hours in an oxygen atmosphere. The powdery material obtained by crushing and screening is the target positive electrode material.

[0044] Example 4 The chemical formula of the sodium ion positive electrode material of Example 4 is Na 0.973 Ni 0.240 Fe 0.343 Mn 0.417 Cu 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 The preparation process refers to Example 1. The difference from Example 1 is that the ratio of Ni to Fe is adjusted, Ni is reduced by 0.01, and Fe is increased by 0.01 accordingly, while the others remain unchanged.

[0045] Example 5 The chemical formula of the sodium ion positive electrode material of Example 5 is Na 0.973 Ni 0.260 Fe 0.333 Mn 0.407 Cu 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 The preparation process refers to Example 1. The difference from Example 1 is that the ratio of Ni to Fe is adjusted, Ni is increased by 0.01, and Mn is correspondingly reduced by 0.01, while the others remain unchanged.

[0046] Example 6 The chemical formula of the sodium ion positive electrode material of Example 6 is Na 0.973 Ni 0.250 Fe 0.323 Mn 0.427 Cu 0.050 Zn0.020 Ti 0.010 Zr 0.020 O 2.2 The preparation process refers to Example 1. The difference from Example 1 is that the ratio of Fe to Mn is adjusted, Fe is reduced by 0.01, and Mn is increased by 0.01 accordingly, while the others remain unchanged.

[0047] Comparative Example 1 The preparation process refers to Example 1, except that the Ti content is reduced from 0.01 to 0, that is, no Ti element is added, and Na 0.973 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.050 Zn 0.020 Zr 0.020 O 2.18 Positive electrode material.

[0048] Comparative Example 2 The preparation process refers to Example 2, except that the Ti content is increased from 0.05 to 0.06 to prepare Na 0.933 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.010 Zn 0.040 Ti 0.060 O 2.22 Positive electrode material.

[0049] Comparative Example 3 Referring to Example 2, the Cu content was reduced from 0.01 to 0, that is, no Cu element was added to prepare Na 0.913 Ni 0.250 Fe 0.33 3Mn 0.417 Zn 0.040 Ti 0.050 O 2.18 Positive electrode material.

[0050] Comparative Example 4: Referring to Example 2, the Zn content was increased from 0.04 to 0.05 to prepare Na 0.913 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.010 Zn 0.050 Ti 0.050 O 2.22 Positive electrode material.

[0051] Comparative Example 5: Referring to Example 3, the Zn content was reduced from 0.01 to 0, i.e., no Zn element was contained, and Na 0.993Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.080 Ti 0.040 O 2.24 Positive electrode material.

[0052] Comparative Example 6: Referring to Example 3, the Cu content was increased from 0.08 to 0.09 to prepare Na 1.033 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.090 Zn 0.010 Ti 0.040 O 2.28 Positive electrode material.

[0053] Comparative Example 7: Referring to Example 4, the ratio of Ni to Fe was further adjusted on the basis of Example 4, the ratio of Ni was further reduced from 0.240 to 0.230, the ratio of Fe was further increased from 0.343 to 0.353, and the others were kept unchanged to prepare Na 0.973 Ni 0.230 Fe 0.353 Mn 0.417 Cu 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 Positive electrode material.

[0054] Comparative Example 8: Referring to Example 5, the ratio of Ni to Fe was further adjusted on the basis of Example 5, the ratio of Ni was further increased from 0.260 to 0.270, and the ratio of Ni was further reduced from 0.407 to 0.397, and the others were kept unchanged to prepare Na 0.973 Ni 0.270 Fe 0.333 Mn 0.39 7Cu 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 Positive electrode material.

[0055] Comparative Example 9: Referring to Example 6, the ratio of Fe to Mn was further adjusted on the basis of Example 6, the ratio of Fe was further reduced from 0.323 to 0.313, the ratio of Mn was further increased from 0.427 to 0.437, and the others were unchanged to prepare Na 0.973 Ni 0.250 Fe 0.313 Mn 0.437Cu 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 Positive electrode material.

[0056] Comparative Example 10 Referring to Example 1, only Mg element (magnesium oxide raw material) was used to replace Cu element (copper oxide raw material), and the other elements remained unchanged to prepare Na 0.973 Ni 0.250 Fe 0.333 Mn 0.417 Mg 0.050 Zn 0.020 Ti 0.010 Zr 0.020 O 2.2 Positive electrode material.

[0057] Comparative Example 11 Referring to Example 1, only the Ca element (magnesium carbonate raw material) was used to replace the Cu element (zinc oxide raw material), and the other elements remained unchanged to prepare Na 0.973 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.050 Ca 0.020 Ti 0.010 Zr 0.020 O 2.2 Positive electrode material.

[0058] Comparative Example 12 Referring to Example 1, only Sn element (tin dioxide raw material) was used to replace Ti element (titanium dioxide raw material), and the other elements remained unchanged to prepare Na 0.973 Ni 0.250 Fe 0.333 Mn 0.417 Cu 0.050 Zn 0.020 Sn 0.010 Zr 0.020 O 2.2 Positive electrode material. Comparative Example 13 Referring to Example 1, only Al element (aluminum oxide raw material) was used to replace 0.02% of Fe element (iron oxide raw material), and the other elements remained unchanged to prepare Na 0.973 Ni 0.250 Fe 0.313 Al 0.020 Mn 0.417 Cu 0.050 Zn 0.020 Sn 0.010 Zr 0.020 O 2.2 Positive electrode material.

[0059] The positive electrode materials of the above-mentioned embodiments and comparative examples are used to prepare button-type batteries and the performance tests of the positive electrode materials and button-type batteries are performed. For example, the prepared fresh materials are assembled into button-type batteries, and a 0.1C first-week capacity test is performed to characterize the capacity performance of the materials; and a 1C cycle retention rate test is performed to characterize the cycle performance of the materials; the powder material is placed in humid air for 12 hours, and the pH before and after the placement is tested, and the absolute value of the pH of the material, as well as the change amount, are used to measure the air stability of the material.

[0060] (1) Preparation of button cells The positive electrode material to be tested: SP (Swiss Super P high conductive carbon black): polyvinylidene fluoride (PVDF, purchased from SOLVAY PVDF5130)) glue (mass fraction 10%, solvent N-methylpyrrolidone (NMP)) is mixed at a mass ratio of 90:5:5 on a dry weight basis, and NMP is added to make a viscous glue. The glue is coated on an aluminum foil (thickness 16µm), and then baked at 120°C in a vacuum drying oven for 12h to obtain a positive electrode sheet (active material surface density 5mg / cm2). A metal sodium sheet (Aladdin) is used as the counter electrode (thickness 300±50µm). Glass fiber (Waterman) was used as the separator (thickness 675 µm) and NaPF6 solution (the solvent was a mixture of EC and DMC, with a volume ratio of EC / DMC = 1:1) (Alfa) with a sodium ion concentration of 1 mol / L was used as the electrolyte. 2032 button cells were assembled in an Ar atmosphere protection glove box. The specific capacity unit is mAh / g.

[0061] (2) Capacity test of button batteries At room temperature of 25°C, according to the voltage range of 2.5-4.2V, charging is performed with a small current of 0.1C, and discharging is performed with a small current of 0.1C. The capacity (unit: mAh / g) of 0.1C is tested; (3) 1C cycle test on button batteries According to the voltage range of 2.5-4.2V, use 1C current for charging and 1C current for discharging. After each discharge, leave it for 2 minutes, repeat the charging and discharging process, repeat the cycle 100 times, calculate the ratio of the 100th discharge capacity to the first discharge capacity, and take it as the capacity retention rate of 100 cycles at 1C; (4) Air stability test of positive electrode materials Sample processing: For untreated fresh samples, perform material pH test; at the same time, place the samples to be tested in a constant temperature and humidity chamber, adjust the temperature to 25°C and the humidity to 50%, and take samples for material pH test after fully exposing for 12 hours; (5) pH test of positive electrode material According to the mass ratio of layered oxide positive electrode material: distilled water = 1:20, take an appropriate amount of positive electrode material and add it to the corresponding amount of distilled water, and stir it magnetically at a speed of 600±20r / min for 10 minutes to mix evenly. Then, after the obtained mixture is allowed to stand for 5 minutes, the pH of the mixture is measured at a constant temperature of 25°C using a pH meter (METTLER TOLEDO pH meter FE22-Standard), which is the pH of the corresponding material.

[0062] (6) SEM test of positive electrode materials All are tested using conventional industry instruments and methods; (7) XRD test of positive electrode materials The X-ray diffractometer (model Bruker D8 ADVANCE) was used to test (λ=1.54056nm) using a copper target (Cu-Kα) (accelerating voltage 40KV, current 40mA), with a range of 10-80 degrees, a step size of 0.02 degrees, a time of 0.2, and a total time of 712 seconds. The O3 phase material was determined based on the reference standard PDF card: PDF#54-0887.

[0063] Table 1 Test results It can be seen from Table 1 that the capacity of each embodiment is ≥161 mAh / g, and at the same time, the cycle retention rate is ≥92.5%, ΔpH ≤0.2, and the pH after placement is ≤12.6. Figure 1 The SEM morphology information of Example 1 shows that the material is a single crystal particle; Figure 2 The XRD data of Example 2 shows that the material is a pure O3 phase structure. Figure 1 , 2 From Table 1, we can draw the following conclusions: (1) When Cu / Zn is within a limited range, the capacity can be effectively improved. If it exceeds the range, it will show low capacity, poor cycle performance, and poor air stability.

[0064] (2) The total amount of Ti / Zr is within a limited range (mainly Ti, Zr may not be present, but Ti cannot be present), which is beneficial to improving cycle performance and air stability; (3) The Ni / Fe / Mn ratio needs to meet the stoichiometric ratio Ni 3 / 12±0.01 Fe 4 / 12±0.01 Mn 5 / 12±0.01 , and the content satisfies Ni+Fe+Mn=1, and the fluctuation range of the single element content is ±0.01. When the fluctuation reaches 0.02, the performance deteriorates significantly; Moreover, it can be seen from the comparative examples that when Cu, Zn, Ti, and Fe are replaced by similar elements such as Mg, Ca, Sn, and Al, respectively, the results all show poor overall performance.

[0065] On the whole, in the embodiment of the present invention, the joint introduction of multiple elements such as Cu, Zn, Ti and Zr transforms the original NiFeMn ternary positive electrode material into a high-entropy positive electrode material of 7 elements, which is more conducive to forming a multi-element synergistic optimization effect and enables the final product to have better comprehensive performance.

[0066] In summary, the sodium ion positive electrode material according to the embodiment of the present invention has a higher capacity while having a lower nickel content, effectively improves the structural stability of the ion positive electrode material, and has better cycle retention performance.

[0067] Other structures and operations of the battery according to the embodiment of the present invention are known to those skilled in the art and will not be described in detail here.

[0068] In the description of the present invention, it is necessary to understand that the terms "center", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "inside", "outside", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0069] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0070] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0071] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A sodium ion positive electrode material, characterized in that: The sodium ion positive electrode material is an O3 phase structure, and the chemical formula of the sodium ion positive electrode material is Na 10 / 12+2x+2y Ni 3 / 12±0.01 Fe 4 / 12±0.01 Mn 5 / 12±0.01 Cu x Zn y M z O 2(1+x+y+z) , wherein Ni+Fe+Mn=1, 0<x≤0.08, 0<y≤0.04, M includes Ti, and the content of M satisfies 0<z≤0.

05.

2. The sodium ion positive electrode material according to claim 1, characterized in that M further contains a Zr element.

3. The sodium ion positive electrode material according to claim 1, characterized in that The sodium ion positive electrode material has a specific capacity of 2.5-4.2V, and a 0.1C reversible specific capacity of ≥160mAh / g.

4. The sodium ion positive electrode material according to claim 1, characterized in that The sodium ion positive electrode material is in single crystal morphology.

5. The sodium ion positive electrode material according to claim 1, characterized in that Under the conditions of 25° C. and 50% humidity, after being fully exposed for 12 hours, the pH value of the sodium ion positive electrode material is ≤12.

6.

6. The sodium ion positive electrode material according to claim 1, characterized in that After 100 cycles at 1C in the voltage range of 2V-4.2V, the capacity retention rate of the sodium ion positive electrode material is ≥92.5%.

7. A method for preparing a sodium ion positive electrode material, characterized in that: The steps include: Mixing a sodium source raw material, a nickel source raw material, an iron source raw material, a manganese source raw material, a copper source raw material, a zinc source raw material and an M source raw material; The mixed raw materials are subjected to a high-temperature solid-phase sintering process to prepare a sodium ion positive electrode material, wherein the sintering temperature is not less than 800° C. The sodium ion positive electrode material is the sodium ion positive electrode material according to any one of claims 1 to 6.

8. The method for preparing a sodium ion positive electrode material according to claim 7, characterized in that: The step of preparing the sodium ion positive electrode material by a high temperature solid phase sintering process of the mixed raw materials comprises: The mixed raw materials are heat-treated at a high temperature of 800°C to 1000°C for 10h to 25h in an oxygen atmosphere; The sodium ion positive electrode material is obtained through crushing and screening.

9. A positive electrode plate for a sodium ion battery, characterized in that: The positive electrode plate comprises the sodium ion positive electrode material described in any one of claims 1-6.

10. A sodium ion battery, characterized in that: A positive electrode sheet for a sodium ion battery comprising the method of claim 9.